TANGGAPAN TERHADAP RANCANGAN UNDANG-UNDANG TENTANG HUKUM MATERIL PERADILAN AGAMA BIDANG PERKAWINAN - Aah Tsamrotul Fuadah (Institut Agama Islam Sahid Bogor, 2021)
Sirri marriage has again become a hot issue in Indonesia, this has emerged when the Draft Law (RUU) was proposed concerning the Material Law of the Religious Courts in the Field of Marriage or popularly known as the Siri Marriage Bill, which threatens the perpetrators of unregistered marriages with criminal sanctions, namely various punishments. ranging from 6 months to three years, and fines starting from Rp. 6 million to Rp. 12 million. This bill invites pros and cons, those who agree think that this is progress because according to them, sirri marriage often only harms the woman and has a negative impact on the offspring of sirri marriages. While those who oppose argue that this bill will actually direct people to legalize adultery.In the study of classical fiqh, sirri marriage is a marriage carried out without a guardian or witness, while the current understanding of sirri marriage is more meaningful that marriage is carried out only in accordance with each religion without being recorded in front of the Office of Religious Affairs. If sirri marriage is interpreted in the first sense, then the scholars agree that marriage is invalid without a guardian and witness. As for sirri marriages which are carried out according to Islam but are not recorded by KUA officers, most of the scholars consider them valid.This is where the problem arises regarding sirri marriage in Indonesia, if this bill is passed then the perpetrators of sirri marriage will be fined or imprisoned. Carrying out marriages legally according to Islamic law as stipulated in article 2 paragraph (1) of Law Number 1 of 1974 is a manifestation of obedience to Allah and His Messenger in matters of marriage. Meanwhile, implementing Article 2 paragraph (2), namely regarding the registration of marriages, is a form of obedience to the leader. However, even though the rules of Allah and His Messenger and humans are very good, there will still be those who break these rules. The proof is that there are still many Muslims who marry without being recorded, even though it is for the benefit of all parties, while benefit is the goal of syara' (maqashid al-shari'ah).So from here it is appropriate for those who carry out unregistered marriages because of financial problems, they must be assisted to carry out their marriage certificate to the Religious Court by litigation free of charge (free of charge). Meanwhile, those who do unregistered marriage for other reasons are encouraged to do itsbat nikah. If you don't want to, then it's only natural to be given sanctions both administratively and with criminal sanctions that can deter you.